Eric D. Perl, Theophany. The Neoplatonic Philosophy of Dionysius the Areopagite, State University of New York Press (SUNY series in ancient Greek philosophy), 2007. 163 p., ISBN-13: 978-0-7914-7111-1 - Caram, Gabriela de los Ángeles (2010)
Fil: Caram, Gabriela de los Ángeles.